Analysis of metabolic washout of positron emitters produced during carbon ion head and neck radiotherapy. Issue 9 (3rd September 2013) - Helmbrecht, Stephan; Enghardt, Wolfgang; Parodi, Katia; Didinger, Bernd; Debus, Jürgen; Kunath, Daniela; Priegnitz, Marlen; Fiedler, Fine
Abstract : Purpose: : Particle Therapy Positron Emission Tomography (PT‐PET) is a suitable method for verification of therapeutic dose delivery by measurements of irradiation‐induced β + ‐activity. Due to metabolic processes in living tissue β + ‐emitters can be removed from the place of generation. This washout is a limiting factor for image quality. The purpose of this study is to investigate whether a washout model obtained by animal experiments is applicable to patient data. Methods: : A model for the washout has been developed by Mizuno et al. [Phys. Med. Biol. 48(15), – (2003)]10.1088/0031‐9155/48/15/302 and Tomitani et al. [Phys. Med. Biol. 48(7), 875–889 (2003)]10.1088/0031‐9155/48/7/305 . It is based upon measurements in a rabbit in living and dead conditions. This model was modified and applied to PET data acquired during the experimental therapy project at GSI Helmholtzzentrum für Schwerionenforschung Darmstadt, Germany. Three components are expected: A fast one with a half life of 2 s, a medium one in the range of 2–3 min, and a slow component of the order of 2–3 h. Ten patients were selected randomly for investigation of the fast component. To analyze the other two components, 12 one‐of‐a‐kind measurements from a single volunteer patient are available. Results: : A fast washout on the time scale of a few seconds was not observed in the patient data. The medium processes showed a mean half life of 155.7 ± 4.6 s. This is in the expected range. Fractions of the activity not influenced by the washout were found. Conclusions: : On the time scale of an in‐beam or in‐room measurement only the medium‐time washout processes play a remarkable role. A slow component may be neglected if the measurements do not exceed 20 min after the end of the irradiation. The fast component is not observed due to the low relative blood filled volume in the brain.